Savings Of Low Income Households In Northern States Of Malaysia - Shakil, Nurul Syifaa Mohd (2020)
Savings is measured as income less expenditure. Households save when there is an excess income to expenditure, and dissave when income decreases or expenditure increases due to unexpected events. This volatile atmosphere leads us to question as to how low-income households save. Studies show that low-income households do save using informal savings mechanisms. The first objective of this study is to assess the amount of household savings with different savings measurements in Malaysia. The second objective is to analyse the determinants of household savings in Malaysia. The third objective is to assess the savings mechanism used by the low income households in the Northern States of Malaysia. The last objective of this study is to assess the impact of risks and other factors towards the savings of low income households in the northern states of Malaysia. In Malaysia, there have been studies on savings behaviour. The recent study used the Households Expenditure Survey (HES) data for the year 2004. To extend the studies of households savings in Malaysia, a new study were done to explore the savings behaviour of households in the Northern States of Malaysia using the HES data for the year 2014, and Research University Team (RUT) survey data for the year 2016. HES data is used to study the savings behaviour of different household groups while the RUT survey data focuses on lowincome households. Both data focus on the Northern States of Malaysia. The study found that the factors affecting the savings behaviour of households in the Northern States of Malaysia are age, gender, educational attainment, employment status, strata and household size. For the case study on low-income households, the study found that low-income households do save